Failed but validated? The effect of market validation on persistence and performance after a crowdfunding failure - Stevenson, Regan; Allen, Jared; Wang, Tang (Journal of Business Venturing, 2022)
We investigate the impact of market validation on persistence and subsequent performance following a specific type of failure (crowdfunding failure). We leverage a mixed methods design, employing a controlled lab experiment with entrepreneurs (Study 1) and a four-year lagged longitudinal field study which combines two archival databases (Study 2). In our experiment, we find that market validation encourages entrepreneur persistence through affective activation and cognition-based action intentions (specifically search and knowledge integration). We also find that another form of validation, expert validation, strengthens this relationship. In our field study, market validation is shown to be a stronger predictor of performance after a crowdfunding failure in comparison to expert validation. We draw from the social proof and wisdom of the crowd perspectives to develop our theoretical model and explain the implications of our findings.